The free maternal health policy: acceptability and satisfaction with quality of maternal health services during pregnancy in rural Northern Ghana (Journal of Health Sciences, 2019)
Introduction: Ghana introduced a maternal health policy in July 2008 to provide free of cost health services to women. However, the utilization of services does not depend on affordability alone but acceptability as well. Acceptability includes attitudes and behaviors of providers and satisfaction with the quality of care. The study explored women’s views and perceptions about attitudes and behaviors of providers and satisfaction with the quality of services under the free maternal health policy in Ghana. In addition, the views and perceptions of providers were examined.Methods: A convergent parallel mixed-methods study was conducted. The study was carried out in the Kassena-Nankana Municipality in Ghana. A structured questionnaire was distributed among women (n=406) who utilized health facilities during pregnancy. Further, focus group discussions (FGDs) with women (n=10) and in-depth interviews with midwives and nurses (n=25) were held. Quantitative data were analyzed using descriptive statistics, while the qualitative data were recorded, transcribed, read, and coded thematically.Results: Women perceived facilities to be clean, especially the smaller ones. Ninety-eight percent of women (n=313/320) perceived providers to be respectful or friendly, and this was mostly confirmed in the FGDs. More than two-thirds of the women (74%, n=300) were also very satisfied or satisfied with the quality of care due to the respect accorded them by providers. Equally, midwives and nurses were satisfied with the quality of care they provided. Nonetheless, providers believed that the unavailability of drugs and supplies, laboratory services, accommodation, and transportation for emergencies reduced women’s satisfaction with services and the quality of care they could provide.Conclusion: The services provided to women during pregnancy were acceptable under the free maternal health policy. There remain challenges in addressing a lack of infrastructure and commodities that affects the quality of care.